A prática de Análise Linguística no livro didático do 7º ano do Ensino Fundamental - Piano, Kalen Franciele (2018)
The linguistic analysis practice (PAL) was proposed for the teaching of Portuguese language, in the 1980s, with the intention of helping students to reflect about the uses of the language in reading and textual production practices. Since then, it has been understood as one of the main cores of teaching the Portuguese language, according prescriptions by pedagogical documents such as the National Curricular Parameters (BRASIL, 1998), and the State Curricular Guidelines (PARANÁ, 2008). The textbooks, in certain ways, try to contemplate this purpose, with various understandings, though. When considering this historical context, the research that I present sustains itself on the theme The linguistic analysis practice in textbooks, delimiting, especially, on the book Araribá Plus Portuguese – 7º grade of Fundamental School II. The concern which originated the dissertation sustains on the question: What is the relationship between the teaching of grammar, PAL and LD Araribá Plus Portuguese – 7º grade? Trying to answer that question, the objective that guides this research is to comprehend, theoretic and methodologically the PAL, analyzing the language working referrals in a textbook of the fundamental school – final years. It is an investigation based on the Applied Linguistic assumptions, according to Moita Lopes’ precepts, (2006); on the interpretative qualitative approach, in line with Bortoni-Ricardo, (2008); and, methodologically, we made an exploratory research, in accordance with Gil (1999), a bibliographic and documental revision. As a result, we understand that some activities have approached the PAL, but most need to be developed by the teacher, because the textbook does not provide such practice, to reach a wider and meaningful level of the language. The students will benefit in their learning from our mediation, developing activities beyond the textbook, by extending the reflection of the language to the context of the student.